Impulsive Buying Behavior in Retailing and Consumer Behavior: A Review - Shrestha, Arpan (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
Purpose: This study aims to provide a comprehensive understanding of impulsive buying behavior by synthesizing diverse research and literature in the field of Retailing and Consumer Behavior. Methods: The study employs a content analysis approach, reviewing a wide range of journal databases and books to gather a diverse collection of research works on impulsive buying behavior. The literature is categorized into various aspects influencing impulsive buying, contributing to the development of a research framework. Findings: The content analysis revealed several key aspects influencing impulsive buying behavior, including psychological triggers, situational factors, and individual characteristics. These findings contribute to a better understanding of the impulsive buying construct and its behavioral elements. Value: This study provides valuable insights for marketing practitioners and scholars, aiding in the development of strategies to address customer impulsiveness effectively. The structured categorization of literature also lays a foundation for future research activities in the domain of impulse buying. DOI: https://doi.org/10.69476/sdpr.2024.v01i01.004